2022
DOI: 10.3390/plants11192573
|View full text |Cite
|
Sign up to set email alerts
|

Essential Oil and Hydrosol Composition of Immortelle (Helichrysumitalicum)

Abstract: The chemical composition of essential oils and hydrosols of immortelle (Helichrysum italicum) stems with leaves obtained by hydrodistillation was identified using gas chromatography coupled with mass spectrometry (GC-MS). One-year-old and two-year-old plants of the same immortelle population, and plants from three Croatian populations, all grown in Slovenia, were included in the study. The main compounds of essential oils of one-year-old and two-year-old plants were α-pinene, α-eudesmol, and rosifoliol. Among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 15 publications
0
6
2
Order By: Relevance
“…Other compounds with somewhat lower yields were nerol, carvacrol, allyl heptanoate, and italidione I (mw = 210) (78.7 mg/L, 78.3 mg/L, 73.1 mg/L, and 70.1 mg/L, respectively). Accordingly, Kunc et al [9] also reported 3-pentanone as one of the major compounds in immortelle hydrosol obtained from one and two-year-old immortelle plants grown in Slovenia (10.0 % and 7.4 %, respectively), but there were no other similarities in the major compounds compared to our sample. Other major compounds in this report were 2,2dimethylnon-5-en-3-one (8.8-13.0 %), 3-octanone (8.0-12.3 %) and α-terpineol (7.6-9.1 %), while in the observed Croatian populations 2,2-dimethylnon-5-en-3-one (14.69-18.40 %) and αterpineol (11.8-19.55 %) were listed as the major compounds.…”
Section: Chloroform Casecontrasting
confidence: 46%
See 2 more Smart Citations
“…Other compounds with somewhat lower yields were nerol, carvacrol, allyl heptanoate, and italidione I (mw = 210) (78.7 mg/L, 78.3 mg/L, 73.1 mg/L, and 70.1 mg/L, respectively). Accordingly, Kunc et al [9] also reported 3-pentanone as one of the major compounds in immortelle hydrosol obtained from one and two-year-old immortelle plants grown in Slovenia (10.0 % and 7.4 %, respectively), but there were no other similarities in the major compounds compared to our sample. Other major compounds in this report were 2,2dimethylnon-5-en-3-one (8.8-13.0 %), 3-octanone (8.0-12.3 %) and α-terpineol (7.6-9.1 %), while in the observed Croatian populations 2,2-dimethylnon-5-en-3-one (14.69-18.40 %) and αterpineol (11.8-19.55 %) were listed as the major compounds.…”
Section: Chloroform Casecontrasting
confidence: 46%
“…[8] Although the chemical analyses of immortelle essential oil have been extensively and thoroughly reported, very few reports paid attention to the chemical composition of hydrosols. [9][10][11][12] The reason for this is probably that the preparation of samples for the chemical analysis of hydrosols is somewhat more difficult than the analysis of essential oils. [12] For quality analysis of hydrosols, nonpolar compounds that are dissolved to a low percentage are usually obtained by repeated liquid-liquid extraction (LLE) with nonpolar solvents of different polarity indices.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Its main components are monoterpene limonene and sesquiterpene hydrocarbons such as α-pinene, α-cedrene, aromadendrene, and β-caryophyllene. 17,18 It is worth mentioning that in one of the reported cases, the patch test with the sesquiterpene lactone mix was also positive, indicating a possible sensitization through this component.…”
Section: Considerations Concerning Some Specific Eosmentioning
confidence: 86%
“…In summary, the aforementioned oil possesses various properties such as anti-allergic, antibacterial and antiaging effects, making it widely used in the cosmetic industry. However, in order to transfer the essential oils to textile materials and ensure their long-lasting effectiveness, different methods need to be employed (Ghayempour and Montazer, 2016; Mehta and MacGillivray, 2016; Ghosh and Chipot, 2015; Kunc et al. , 2022).…”
Section: Introductionmentioning
confidence: 99%